THE USE OF REDW STRATEGY IN IMPROVING SECOND SEMESTER STUDENTS’ READING COMPREHENSION ACHIEVEMENT AT BATURAJA UNIVERSITY - Nopa Yusnilita (ELTE Journal (English Languange Teaching and Education), 2014)
Abstract The objective of this study was conducted to find out whether or not there is significance difference of second semester students’ reading comprehension achievement between students who are taught using REDW strategy and those who are taught by using conventional strategy. The population of the study was the third semester of English education study program at Baturaja University in the academic 2010 – 2011 consisting of 270 students. From the population, 60 students were taken as her research sample. 30 students represent an experimental class and the rest of them were as a control class. The samples were taken by using cluster random sampling. In carrying out the research, the writer used a factorial group design.The data distributions were considered normal. It was proved by statistics calculation of normality test which shows that p-output (.092 and .447) were higher than a (.05). Then based on the calculation of Levene Statistic by using SPSS 15, it was found that the p-value was .223. The samples were considered homogeneous whenever the p-value is higher than α (.05). It means that the samples taken from experiment and control group were homogeneous. Based on the result of the statistics calculation using independent t-test found in SPSS 15, it was found that the p-output was .126 and it was higher than α (.05). It means that H1 is rejected. From the result of the test, it can be shown that the used of REDW strategy can be improve students reading comprehension achievement. Key words: Reading Comprehension, REDW